Halal Tourism in Indonesia: Does it attract only Muslim Tourists? - Winarti, Oktifani (Jurnal Studi Komunikasi, 2017)
Indonesian Halal Tourism became a raising mode to attract Muslim Tourist by Ministry of Tourism Republic Indonesia. Indonesia, as a non-Muslim country by nation ideology, tries to highlight the spiritual spirit of Islam as a culture to attract more tourists and put it into physical practice by having more tourism hospitalities; such as Halal Hotel that has Halal certification, which provides less or even none of alcohol beverages and serves only food based on Halal dietary. Indonesia in developing tourism brand of â€œIndonesia The Halal Wondersâ€ would possibly lead into positive and negative possibilities. This article used literature review to reach data about Halal tourism in Indonesia. It has a tendency for tourism halal markets to lose the customers that are not Muslim travellers.Keywords: Halal Tourism, Indonesia, Muslim, Tourist